Analisis sedimen dan perubahan garis pantai utara pulau rangsang kabupaten kepulauan meranti - Lilian, Anna; ', Mubarak; ', Rifardi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
The main purpose of this study was to reveal the depositional environmentand the movement of coastline. This study was conducted in January 2013 innorthern part of Rangsang Island, Meranti District. Sediment samples were takenfrom 11 station sand analyzed by using mechanical granular method. The methodof remote sensing linear regression was used to determine the movement ofcoastline. The result of study show that the surface bottom sediment ischaracterized by sand and mud fractions, and is dominated by bottom characterof sand. The study area was a transitional area where waves and currents werepredicted to change frequently through not too significant. The currents strengthtend to move with the fluctuations. The average change of the coastline during thepast 13 years (2000 to 2013) was 7,455 m/yr with the greatest changes occurredat station 7, i.e. Kedabu Rapat Village, with 8.54 m/yr. The speed movement ofcoastline was marked by the destruction of land cover in the north along the coastof the Rangsang Island as indicated by destruction of mangrove forests andvegetation coast, the sinking of jetty, roads and houses as well as the erosion.Kata kunci: movement of coastline, sediment coastal, Rangsang Island, abration.